Basophil reactivity, wheal size, and immunoglobulin levels distinguish degrees of cow's milk tolerance - Ford, Lara S.; Bloom, Katherine A.; Nowak-Węgrzyn, Anna H.; Shreffler, Wayne G.; Masilamani, Madhan; Sampson, Hugh A. (Journal of allergy and clinical immunology, 2013)
In our previous study about 75% of children with cow's milk allergy tolerated baked milk products, which improved their prognosis and quality of life. We sought to identify biomarkers of varying degrees of clinical tolerance among a cohort of children with cow's milk allergy. One hundred thirty-two subjects were initially classified as baked milk–reactive, baked milk–tolerant, or having “outgrown milk allergy” based on the results of oral food challenges. The baked milk–tolerant group was then divided into 3 groups based on the amount and degree of heat-denatured milk protein that they could tolerate. Serum was analyzed for allergen-specific IgE and IgG4 levels, basophil reactivity was assessed in whole blood stimulated with serial 10-fold dilutions of milk protein, and skin prick tests (SPTs) were performed to commercial milk extract. Activated basophils were defined by using flow cytometry as CD63brightCD203c+CD123+HLA-DRdim/−CD41a−lineage−. Data were analyzed by using the Jonckheere-Terpstra test. Significant differences across the 5 clinical groups were seen for median casein- and milk-specific IgE levels, casein-specific IgG4 levels, and casein IgE/IgG4 ratios; milk-specific to nonspecific basophil activation ratio, median basophil reactivity, and spontaneous basophil activation (CD203c expression after stimulation with RPMI); and milk SPT wheal diameters. Casein- and milk-specific IgE level, milk-specific basophil reactivity, and milk SPT wheal diameter are all significantly greater among patients with milk allergy who react to baked milk than among those who tolerate it. The majority of patients with milk allergy are able to tolerate some forms of baked milk in their diets. Different phenotypes of children with cow's milk allergy can be distinguished by casein- and milk-specific IgE levels, milk-specific basophil reactivity, and milk SPT mean wheal diameters. Spontaneous basophil activation is greater among patients with more severe clinical milk reactivity.